2019
DOI: 10.1177/1403494819852847
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment among young people and mental health: A systematic review

Abstract: Aim: The aim of this systematic review is to obtain a better understanding of the association between unemployment among young people and mental health. Methods: After screening the title and abstract of 794 articles drawn from four electronic databases, 52 articles remained for full-text reading. Of these, 20 studies met the inclusion criteria and were assessed on methodological quality. All steps were performed independently by two reviewers. Finally, a total of 17 articles were included in the syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 43 publications
4
50
0
3
Order By: Relevance
“…The use of longitudinal data will facilitate improved confounder control, particularly by allowing for baseline control of the outcome. A recent systematic review of the effects of unemployment on the mental health of young people reported that when confounders, including baseline mental health were controlled for, the effect estimates decreased and led to mixed results [48]. This indicates the importance of consistently controlling for appropriate confounders.…”
Section: Discussionmentioning
confidence: 99%
“…The use of longitudinal data will facilitate improved confounder control, particularly by allowing for baseline control of the outcome. A recent systematic review of the effects of unemployment on the mental health of young people reported that when confounders, including baseline mental health were controlled for, the effect estimates decreased and led to mixed results [48]. This indicates the importance of consistently controlling for appropriate confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Involuntary underemployment and/or unemployment (UUE) is associated with poor mental health [ 12 , 13 ]. Multiple factors derived from the UUE situation, for example, economic anguish and joblessness, employment insecurity, continuous underlie feelings of failure, which severely may lead to common mental health symptoms such as depression, anxiety, and stress [ 14 , 15 ]. And these mental health problems significantly reduce productivity and quality of life and responsible for most suicide casualties [ 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Self-employment (including own-account workers) involves several risks and uncertainties that can potentially harm the psychological wellbeing of an individual, yet some self-employed tend to report high levels of psychological wellbeing (Baron et al, 2016). Similarly, recent studies have highlighted the psychological distress of unemployment (Bartelink et al, 2020;Bonanomi & Rosina, 2020;Farré et al, 2018). However, questions have been asked whether any job is better than no job that is concerning the effects of unemployment and poor quality jobs on psychological health?…”
Section: Introductionmentioning
confidence: 99%